Scroll, Buy, Reflect: Building a Communication Framework for Sustainable Beauty on TikTok - Fauziah, Farisa Najmi; Alamsah, Nadiny Salwaa; Saragih, Irene Brenda Patricia (Communicare : Journal of Communication Studies, 2025)
TikTok is reshaping beauty consumption among Gen Z, driving impulsive purchasing patterns that often lead to regret, waste, and short-lived product use. In Indonesia, this dynamic is intensified by algorithmic targeting, influencer-driven credibility, and the accelerating cycle of viral aesthetics. A survey of 240 Gen Z TikTok users found that 82.09% regretted purchasing trending beauty products, and 78.61% reported owning viral items that were ultimately unused or discarded. These findings expose a persistent gap between consumers’ growing sustainability awareness and their actual purchasing behavior, suggesting that emotional reactivity continues to override rational decision-making in digital beauty consumption. To examine the drivers behind this gap, the study applies the Socio-Ecological Model (SEM) and integrates quantitative survey data with insights from eight in-depth interviews involving marketers, influencers, scholars, and Gen Z users. The analysis identifies regret as a pivotal emotional trigger that can facilitate behavioral change when appropriately addressed through communication. Based on these insights, the study proposes a strategic communication framework targeting all five SEM levels to encourage reflection, reduce overconsumption, and foster responsible digital habits. The paper argues that communication functions not only as a corrective mechanism but also as a catalyst for sustainable consumption aligned with SDG 12.